2013
DOI: 10.4161/cbt.23626
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hsp90 inhibitor NVP-AUY922 radiosensitizes prostate cancer cells

Abstract: Outcomes for poor-risk localized prostate cancers treated with radiation are still insufficient. Targeting the "non-oncogene" addiction or stress response machinery is an appealing strategy for cancer therapeutics. Heat-shock-protein-90 (Hsp90), an integral member of this machinery, is a molecular chaperone required for energy-driven stabilization and selective degradation of misfolded "client" proteins, that is commonly overexpressed in tumor cells. Hsp90 client proteins include critical components of pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…While more potent inhibitors such as AUY922 are currently being developed and show promise as single agents (Samuel et al 2010, Centenera et al 2012, recent evidence of additive or synergistic activity between 17-AAG and cytotoxic agents or specific molecular therapeutics provides a promising new avenue of clinical development for this drug . In preclinical prostate cancer studies, 17-AAG or AUY922 combined with ionizing radiation has demonstrated supra-additive reductions in tumor growth and clonogenicity (Enmon et al 2003, Ochel & Gademann 2006, Gandhi et al 2013. Likewise, AUY922 sensitized CRPC prostate cancer cells lines to treatment with docetaxel chemotherapy (Ku et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While more potent inhibitors such as AUY922 are currently being developed and show promise as single agents (Samuel et al 2010, Centenera et al 2012, recent evidence of additive or synergistic activity between 17-AAG and cytotoxic agents or specific molecular therapeutics provides a promising new avenue of clinical development for this drug . In preclinical prostate cancer studies, 17-AAG or AUY922 combined with ionizing radiation has demonstrated supra-additive reductions in tumor growth and clonogenicity (Enmon et al 2003, Ochel & Gademann 2006, Gandhi et al 2013. Likewise, AUY922 sensitized CRPC prostate cancer cells lines to treatment with docetaxel chemotherapy (Ku et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Checkpoint arrest mainly at G2/M phase has also been suggested as a cause of radiosensitization with Hsp90 inhibitors (1924, 36). Radiosensitization effect in vivo by Hsp90 inhibitors has also been demonstrated (14, 21, 23). These data strongly suggest that targeting Hsp90 with its inhibitors represents a promising strategy for enhancing the sensitivity of cancer cells to radiation (1924).…”
Section: Discussionmentioning
confidence: 96%
“…Alternatives to 17-AAG have been developed [19], and several promising molecules, including AUY922 [5] and Ganetspib (STA-9090) [20], are in current clinical trials as monotherapies. However, there are still concerns about the HSR triggered by blocking the ATP-Hsp90 interaction, as it provides tumor cells an opportunity to survive.…”
Section: Why Have So Many Classical Hsp90 Inhibitors Failed In the CLmentioning
confidence: 99%
“…Over the past 10 years, 15 different Hsp90 inhibitors have been tested in clinical trials [3][4][5]. However, only three remain active as mono-chemotherapy regiments [6].…”
mentioning
confidence: 99%